UJI AKTIVITAS ANTIOKSIDAN EKSTRAK ETANOL HERBA PEGAGAN (Centella asiatica (L.) Urb) DENGAN METODE FOSFOMOLIBDAT - Salamah, Nina; Farahana, Liani (Pharmaciana, 2014)
Antioxidant compound extends widely used to prevent degenerative disease. Centella asiatica(L.) Urb or known as pegagan is a plant which grown in Indonesia and itâs leaves contain somecompounds reported to have antioxidant activities. The research aimed to know antioxidant activity ofethanolic extract of pegagan herbs by mechanism of reducing power. The antioxidant activity analyzedusing visible spectrophotometric with phosphomolybdate method. Antioxidant activity of ethanolicextract of pegagan was expressed as mg quercetin equivalence/gram extract). The result showed thatusing this method the ethanolic extract of pegagan activity had antioxidant activity which is43.198 Â± 2.048 mg mgQE/gram extract.